Evaluation of preventable adverse drug reactions by implementation of the nationwide network of prospective drug utilization review program in Korea - Lee, Jimin; Noh, Yoojin; Lee, Sukhyang (PLoS ONE, 2018)
Background A prospective Drug Utilization Review (DUR) program has been implemented in Korea to improve the quality and safety of medication use. Objective To evaluate the influence of the DUR program in reducing incidence of preventable adverse drug reactions (pADRs). Methods This study was performed using administrative data from the Health Insurance Review and Assessment Service (HIRA). The claims data for all adult patients with adverse drug events (ADE)-related diagnoses from 2009 to 2014 were obtained. Incidence rates of first-time and repeat pADRs prior to and after DUR program implementation were evaluated. Quarterly trends in incidence rates of overall ADE, allergic reactions, and ADRs were analyzed. Results Data extraction covering the period from 2009 to 2014 led to the identification of 3,927,662 records. First-time pADR rates decreased gradually after implementation of the DUR program (change in slope: -0.016, p = 0.02). The program had a similar influence on repeat pADR rates (change in slope: -0.006, p0.01). The program did not decrease rates of first-time or repeat allergic reactions (change in slope: 0.018, p = 0.07 and 0.003, p = 0.04, respectively). In the cohort aged 65 years, first-time pADR rate reduction was significant (28.2% [27.1–29.3] in 18 years, and 19.8% [18.1–21.5] in 19–64 years). In contrast, first-time pADR rate was increased by 0.6% [-0.7–1.9] in patients 65 years. Conclusion Implementation of the prospective DUR program effectively reduced the number of pADRs. In the future, to reduce non-preventable ADRs such as allergic reactions, provision of clinical information including allergy history should be added to the DUR program.
Keywords: Adolescent; Aged; Drug-Related Side Effects and Adverse Reactions; Electronic Health Records; Female; Humans; Insurance, Health; Male; Middle Aged; Republic of Korea; Young Adult